1972
DOI: 10.1172/jci106824
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aldosterone Concentration at Delivery and during the Newborn Period

Abstract: A B S T R A C T Aldosterone concentrations in plasma of women on normal sodium intake undergoing cesarean section were 3.7 ±1.4 ng/100 ml (mean ±1 SD). These values were significantly lower (P <0.001) than those observed in mothers on normal sodium diet, delivered by the vaginal route (14.9 +7.0 ng/100 ml). A significant elevation (P < 0.001) of the concentrations was found if the mothers had been on sodium restriction and/or diuretics (44.9 ±24.2 ng/100 ml). In supine position, adult nonpregnant subjects have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1
3

Year Published

1978
1978
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(33 citation statements)
references
References 59 publications
5
24
1
3
Order By: Relevance
“…These results are in accordance with previous studies that have reported high levels of aldosterone in neonates (10) compared with their mothers (21). Although aldosterone has been previously shown to cross the placental barrier from the mother to the fetus (20), highest aldosterone levels detected in the cord blood are consistent with de novo synthesis in the fetal adrenal gland, given the very early expression of the aldosterone synthase gene starting from 13 gestational weeks (22).…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with previous studies that have reported high levels of aldosterone in neonates (10) compared with their mothers (21). Although aldosterone has been previously shown to cross the placental barrier from the mother to the fetus (20), highest aldosterone levels detected in the cord blood are consistent with de novo synthesis in the fetal adrenal gland, given the very early expression of the aldosterone synthase gene starting from 13 gestational weeks (22).…”
Section: Discussionsupporting
confidence: 92%
“…Newborn animals and humans have higher aldosterone concentrations than adults. 19,20 Preterm infants with a mean gestational age of 31 weeks who did not receive sodium supplementation showed an increase in plasma aldosterone concentration and urinary aldosterone excretion over the first few weeks of life, followed by a decrease over the following 2 weeks. Conversely, no changes in these measurements were observed in infants who received supplemental sodium when compared with full-term newborn infants.…”
Section: Discussionmentioning
confidence: 99%
“…Accompanying these findings, histochemical changes such as an increased activity of glucose-6-phosphate dehydrogenase means that the glomerular cells of the fetus can react functionally to specific stimulus (7). The condition of sodium restriction of the mother alters the aldosterone secreting rate of the human fetus (1,2,6). Although the degree of sodium restriction given to the mother in this experiment is standard in the rat, the sodium restriction experiment in the rat must be repeated not only morphologically but also quantitatively, changing the degree of sodium restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone has already been detected in the fetuses of human, chicken, mice and guinea pigs (1,2,3,4,6,8), and the zona glomerulosa of the fetus is thought to be functional in the late stage of gestation (1,2,5,14). According to our previous study, (12,13,14), the zona glomerulosa of fetal rats is almost well differentiated in the latest stage of gestation.…”
mentioning
confidence: 82%